Percutaneous Peripheral Nerve Stimulation of the Medial Branch Nerves for the Treatment of Chronic Axial Back Pain in Patients After Radiofrequency Ablation - Deer, Timothy R (Pain Med, 2021)
OBJECTIVE: Lumbar radiofrequency ablation is a commonly used intervention for chronic back pain. However, the pain typically returns, and though retreatment may be successful, the procedure involves destruction of the medial branch nerves, which denervates the multifidus. Repeated procedures typically have diminishing returns, which can lead to opioid use, surgery, or implantation of permanent neuromodulation systems. The objective of this report is to demonstrate the potential use of percutaneous peripheral nerve stimulation (PNS) as a minimally invasive, nondestructive, motor-sparing alternative to repeat radiofrequency ablation and more invasive surgical procedures. DESIGN: Prospective, multicenter trial. METHODS: Individuals with a return of chronic axial pain after radiofrequency ablation underwent implantation of percutaneous PNS leads targeting the medial branch nerves. Stimulation was delivered for up to 60 days, after which the leads were removed. Participants were followed up to 5 months after the start of PNS. Outcomes included pain intensity, disability, and pain interference. RESULTS: Highly clinically significant (≥50%) reductions in average pain intensity were reported by a majority of participants (67%, n = 10/15) after 2 months with PNS, and a majority experienced clinically significant improvements in functional outcomes, as measured by disability (87%, n = 13/15) and pain interference (80%, n = 12/15). Five months after PNS, 93% (n = 14/15) reported clinically meaningful improvement in one or more outcome measures, and a majority experienced clinically meaningful improvements in all three outcomes (i.e., pain intensity, disability, and pain interference). CONCLUSIONS: Percutaneous PNS has the potential to shift the pain management paradigm by providing an effective, nondestructive, motor-sparing neuromodulation treatment.